The Influence Of Product Innovation And Product Quality On Competitive Advantage Of Al Mifta Songket Products In Mesjid Lama Village, Talawi District, Batubara Regency - Khairiah, Putri; Sari, Dian Septiana (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This research aims to determine how much influence product innovation and product quality have on competitive advantage in marketing songket products to consumers. This research also uses a quantitative approach with a technique using the Slovin formula, involving 91 respondents from a population of 2019-2024 of 1,043. Data were collected through questionnaires and analyzed using multiple regression analysis to test the partial and simultaneous effects of independent variables on competitive advantage. The findings of this research indicate that product innovation and product quality partially and simultaneously have a positive and significant effect on competitive advantage. Among these variables, product innovation and competitive advantage emerge as the most dominant influences. MSME actors need to implement sustainable innovation policies and maintain product quality standards to remain relevant and in demand by the market. In practice, these results encourage the government and MSME supporting institutions to provide training in design innovation and quality management. Al Mifta's competitive advantage can be explained by product innovation and product quality by 35.50% and the remaining 64.5% can be explained by other elements.